Alternative energy storage and energy harvesting methods for parallel hybrid light aircraft. (2016) - Olsen, John; Page, John; Vulovic, Zoran
To reduce an aircraft's fuel consumption, it is important to keep its weight to a minimum. In this work, we argue that it should be possible to design a light, hybrid powered aircraft with a weight similar to that of a conventionally powered aircraft. Having already identified the windmilling propeller as a means of harvesting energy during descending phases of aircraft operations (which is mission dependent), we consider the use of turbines and thermoelectric generators as an additional means of energy harvesting. These further means have the advantage of being essentially mission independent. Alternative possibilities for energy storage other than using (lithium-ion) batteries are also considered such as flywheels and pneumatic cylinders. We discuss energy saving strategies for engine start-up, engine run-up and taxiing. Finally, we carry out a simple power balance matching the power required to the power available to estimate the extent to which fuel consumption is reduced in the hybrid powered aircraft compared to the conventionally powered aircraft.